2012
DOI: 10.1073/pnas.1200498109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of invariant natural killer T cells by lipid excess promotes tissue inflammation, insulin resistance, and hepatic steatosis in obese mice

Abstract: Obesity triggers a low-grade systemic inflammation, which plays an important role in the development of obesity-associated metabolic diseases. In searching for links between lipid accumulation and chronic inflammation, we examined invariant natural killer T (iNKT) cells, a subset of T lymphocytes that react with lipids and regulate inflammatory responses. We show that iNKT cells respond to dietary lipid excess and become activated before or at the time of tissue recruitment of inflammatory leukocytes, and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 67 publications
7
162
2
1
Order By: Relevance
“…As IFN-γ has been associated with insulin resistance in cultured adipocytes (56,57) and in vivo (14,58), these findings suggest that, in contrast to the protective role we observed under LFD conditions, iNKT cells could contribute to the development of insulin resistance under other conditions. Indeed, some recent reports indicate that depletion of iNKT cells can improve insulin sensitivity under HFD conditions (59)(60)(61). The exact role of iNKT cells under HFD conditions is, however, unclear, as other studies, and the present study, failed to detect a prominent effect of iNKT cell depletion on glucose homeostasis (26)(27)(28).…”
Section: Methodscontrasting
confidence: 55%
“…As IFN-γ has been associated with insulin resistance in cultured adipocytes (56,57) and in vivo (14,58), these findings suggest that, in contrast to the protective role we observed under LFD conditions, iNKT cells could contribute to the development of insulin resistance under other conditions. Indeed, some recent reports indicate that depletion of iNKT cells can improve insulin sensitivity under HFD conditions (59)(60)(61). The exact role of iNKT cells under HFD conditions is, however, unclear, as other studies, and the present study, failed to detect a prominent effect of iNKT cell depletion on glucose homeostasis (26)(27)(28).…”
Section: Methodscontrasting
confidence: 55%
“…Although the pathological impact of both innate and adaptive immune cells, including myeloid cells, B cells, T cells, and natural killer T (NKT) cells, has been documented in DIO models (1,7,9,11,12,28,29), the molecular signaling pathways that mediate their effects remain largely unexplored and unclear. In the present study, we have identified the transcription factor Stat3 as an important mediator of T-cell-driven inflammation in adipose tissue of DIO mice.…”
Section: Discussionmentioning
confidence: 99%
“…NKT cells react to lipid antigens presented on CD1d, which results in the secretion of various cytokines (IL-4, IL-10, IFN-g, and TNF-a) that may elicit Th1, Th2, and Treg responses. Experiments with mice with loss-and gain-offunction in NKT activity revealed a gamut of outcomes ranging from beneficial (21)(22)(23)(24)(25), to null (26), to detrimental (27)(28)(29) effects of NKT cells on metabolism. These divergent effects may result from the various strategies applied (CD1d 2/2 that affects all NKT cells vs. Ja18 2/2 that affects only type 1 NKT cells), various diets, various durations, or other local, yet not identified factors.…”
Section: Immune Cells Orchestrate the Outcome Of At Inflammationmentioning
confidence: 99%